DIFFERENT VARIABLES INVESTIGATION OF ATHLETIC IDENTITY IN TEAM SPORT - Çetinkaya, Turan; Yetim, Azmi (PEOPLE: International Journal of Social Sciences, 2015)
The aim of this study is to determine the relationship of athletic identity between different variables such as license period, sport branch and the conditions of national players.The research group has been established of 485 athletes who struggle on the top platform in various sport branches in Turkey leagues. As data collection tool,the athlete identity scale was used in research.At the evaluation of data: frequency, mean, standard deviation, scales, Cronbach Alpha reliability coefficient,t-test for independent groups, one-way analysis of variance for independent groups (ANOVA), simple correlation analysis and simple linear regression analysis methods were used. According to the findings, athlete identity varies significantly for the license period and nationalities of variables but does not cause any difference for sport branch.The findings obtained from the study may suggest that it is possible to create a productive sport life with a strong athlete identity.